The Development of a Live Air Cleaner as Indoor Garden for an Unventilated Air Conditioned Room - Satwiko, Prasasto; Suhodo, YP; Silvia S, Israni; Istiadji, A Djoko; Sekarlangit, Nimas; Retnaningati, Dewi (Journal of Architectural Research and Design Studies, 2020)
Urban temperatures continue to increase due to urban heat island and global warming. Air temperatures in warm, humid tropical cities have exceeded 32oC. To achieve thermal comfort in buildings, people adopted air conditioners (ACs) that can consume more than 40% of the building's electrical energy. Air conditioning is often not accompanied by a supply of fresh outdoor air to minimize heat gain from the warm outdoor air. In that unventilated room, the CO2 concentration easily exceeds 1,000 ppm and causes discomfort. Plants such as Dracaena sanderiana require CO2 for photosynthesis. At the same time, they produce O2. Dracaena sanderiana has the potential to keep CO2 concentrations in the room for not exceeding the comfort limit. That plant can be integrated into architectural elements, both interior and exterior (combined with windows or facades), in the form of a "living air purifier" or Live Air Cleaner (LAC). This research developed a LAC in the form of an interior garden that can be used as an interior architectural element. The application of LAC helps to save the electrical energy of unventilated air-conditioned rooms while preventing the room CO2 concentration from reaching the maximum limit of indoor CO2 level acceptable to humans. The research adopted experimental methods using three experiment chambers to measure the Dracaena sanderiana’s CO2 absorption efficiency. The experiments found that Dracaena sanderiana had a unique performance, which should be considered when it is used as a live air cleaner. Though this plant absorbs CO2, its efficiency is low. Sufficient volume of Dracaena sanderiana is needed if it is to reduce indoor CO2 concentration. Keywords: Live Air Cleaner, Air conditioning, Indoor garden, CO2 absorption